صورة المطر في التراث الشعبي السّوفي وعلاقته بالحياة الاجتماعية )دراسة موضوعية - براهمي وفاء; تيته خولة; طيباني هناء (University of El-Oued جامعة الوادي, 2025)
هذه المذكرة دراسة صورة المطر بوصفها رمزًا غنيًا بالدلالات في الشعر الشعبي بمنطقة وادي سوف، حيث يُمثل المطر عنصرًا محوريًا في الحياة اليومية والوجدان الجمعي لسكان المنطقة نظرًا لطبيعتها الصحراوية وشحّ الموارد المائية. تهدف الدراسة إلى تحليل الأبعاد الرمزية والجمالية لصورة المطر، وكيف يتجلى في القصائد الشعبية كرمز للخصب، والأمل، والتجدد، وفي أحيان أخرى كرمز للحنين، والرزق، وحتى للحزن أو الانتظار. تستند الدراسة إلى نصوص شعرية محلية تم جمعها من رواة وشعراء شعبيين بالمنطقة، وتُحلَّل وفق مقاربات نقدية تتداخل فيها الأنثروبولوجيا مع التحليل الأدبي. كما تُبرز المذكرة العلاقة الوثيقة بين البيئة الصحراوية والإبداع الشعبي، حيث يشكل المطر رمزًا مركزيًا في بناء الصور الشعرية التي تعكس الوجدان السوفي وارتباطه الوثيق بالطبيعة وتقلباتها. Résumé : فرنسية أو انجيلزية This memorandum deals with the study of the image of rain as a symbol rich in connotations in popular poetry in the Wadi Souf region, where rain represents a pivotal element in the daily life and collective conscience of the region’s residents due to its desert nature and scarcity of water resources. The study aims to analyze the symbolic and aesthetic dimensions of the image of rain, and how it appears in popular poems as a symbol of fertility, hope, and renewal, and at other times as a symbol of nostalgia, livelihood, and even sadness or waiting. The study is based on local poetic texts collected from popular narrators and poets in the region, and is analyzed according to critical approaches in which anthropology overlaps with literary analysis. The memorandum also highlights the close relationship between the desert environment and popular creativity, as rain constitutes a central symbol in constructing poetic images that reflect the Soviet conscience and its close connection to nature and its fluctuationstransmitter of eloquent speech that is suitable for citation.
مذكرة .ماستر . أدب شعبي . 2025
Keywords: الشعر الشعبي، صورة المطر، الرمزية، وادي سوف، البيئة الصحراوية; Keywords: Folk poetry; rain image; symbolism; Wadi Souf; desert environment